Pounding tools in HWK EE and EF-HR (Olduvai Gorge, Tanzania): Percussive activities in the Oldowan-Acheulean transition. Issue 120 (July 2018) - Arroyo, Adrián; de la Torre, Ignacio
Abstract: In this paper, we present pounded objects from excavations at HWK EE and EF-HR, which are studied from macro and microscopic perspectives. Analysis of HWK EE revealed one of the largest collections of percussive objects from Olduvai Gorge, while excavations at EF-HR have allowed us to recover a much wider collection of percussive tools than previously recorded. Differences are observed between the two localities. At the Acheulean site of EF-HR, percussive tools were predominantly used in the production of flakes and large cutting tools (LCTs). At the Oldowan site of HWK EE, the tool repertoire probably related to a wider range of activities, including bone breaking and bipolar knapping. Comparison of these two assemblages, potentially produced by different hominin species, helps provide a wider picture of pounding activities during the Oldowan-Acheulean transition at Olduvai Gorge.